2014
DOI: 10.1111/1574-6941.12282
|View full text |Cite
|
Sign up to set email alerts
|

Methane emission and dynamics of methanotrophic and methanogenic communities in a flooded rice field ecosystem

Abstract: Methane emissions, along with methanotrophs and methanogens and soil chemical properties, were investigated in a flooded rice ecosystem. Methane emission increased after rice transplantation (from 7.2 to 552 mg day(-1) m(-2) ) and was positively and significantly correlated with transcripts of pmoA and mcrA genes, transcript/gene ratios of mcrA, temperature and total organic carbon. Methane flux was negatively correlated with sulfate concentration. Methanotrophs represented only a small proportion (0.79-1.75%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
79
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 90 publications
(121 reference statements)
16
79
2
4
Order By: Relevance
“…Thus, differences in CH 4 emissions among rice varieties should primarily stem from the effect of rice plants on the belowground processes (CH 4 production and/or oxidation in soil). These results are in consistent with the increasing recognition of the importance of belowground processes over methane emissions (Aulakh et al, 2001;Gutierrez et al, 2014;Kerdchoechuen, 2005;Lee et al, 2014). Relative to the indirect effect of aboveground plant traits on the CH 4 emission, rice roots play an important role in all CH 4 -related processes, contributing to the direct impact on the CH 4 emission.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, differences in CH 4 emissions among rice varieties should primarily stem from the effect of rice plants on the belowground processes (CH 4 production and/or oxidation in soil). These results are in consistent with the increasing recognition of the importance of belowground processes over methane emissions (Aulakh et al, 2001;Gutierrez et al, 2014;Kerdchoechuen, 2005;Lee et al, 2014). Relative to the indirect effect of aboveground plant traits on the CH 4 emission, rice roots play an important role in all CH 4 -related processes, contributing to the direct impact on the CH 4 emission.…”
Section: Discussionsupporting
confidence: 87%
“…Currently, the model for CH 4 emissions under rice cultivation is that CH 4 is formed in the soil away from the roots and diffuses through the soil to the rice root, where it is expelled via the aerenchyma in the roots (19,32,36). We used our dataset to examine the abundances of taxa related to CH 4 cycling.…”
Section: Cultivation Practice Results In Discernible Differences In Tmentioning
confidence: 99%
“…Lee et al (20) also showed that the methane-oxidizing bacterial community changed between different rice-growing stages in a flooded paddy field in Korea. A parallel study to the present study demonstrated that the abundance of methane-oxidizing bacteria in rice roots decreased under elevated [CO 2 ], which interacted with elevated soil temperature in the paddy field (31).…”
Section: Discussionmentioning
confidence: 95%
“…The copy number of the pmoA gene in the upper soil layer correlated with methane emission, whereas no correlation was observed in the lower soil layer at the PI stage (data not shown), indicating the greater contribution of methane-oxidizing bacteria in the upper, than in the lower soil layer to methane emission. Previous studies used the ratio of the mcrA / pmoA genes (14) or mcrA / pmoA transcripts (20) as a parameter to assess methane emission in paddy fields. In the present study, although no correlation was found at the MR stage, possibly due to large variations in methane emission rates (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation